Linking the westernised oropharyngeal microbiome to the immune response in Chinese immigrants - Guo, Jing; Zhang, Xiaoping; Saiganesh, A.; Peacock, C.; Chen, Sue; Dykes, Gary; Hales, B.J.; Le Souëf, P.N.; Zhang, Brad (BMC, 2020)
Background: Human microbiota plays a fundamental role in modulating the immune response. Western environment and lifestyle are envisaged to alter the human microbiota with a new microbiome profile established in Chinese immigrants, which fails to prime the immune system. Here, we investigated how differences in composition of oropharyngeal microbiome may contribute to patterns of interaction between the microbiome and immune system in Chinese immigrants living in Australia.